Reading intervention with a growth mindset approach improves children’s skills - Andersen, Simon Calmar (Proc Natl Acad Sci U S A, 2016)
Laboratory experiments have shown that parents who believe their child’s abilities are fixed engage with their child in unconstructive, performance-oriented ways. We show that children of parents with such “fixed mindsets” have lower reading skills, even after controlling for the child’s previous abilities and the parents’ socioeconomic status. In a large-scale randomized field trial (N(classrooms) = 72; N(children) = 1,587) conducted by public authorities, parents receiving a reading intervention were told about the malleability of their child’s reading abilities and how to support their child by praising his/her effort rather than his/her performance. This low-cost intervention increased the reading and writing achievements of all participating children—not least immigrant children with non-Western backgrounds and children with low-educated mothers. As expected, effects were even bigger for parents who before the intervention had a fixed mindset.